Evaluación del daño causado por plagas y enfermedades mediante imágenes Multiespectrales en el cultivo de Chocho (Lupinus Mutabilis) en la parroquia de San Juan de Pastocalle - Ugsha Cuyo, Frank Alex (2023)
The investigation it was made in the Ordoño´s estate, in the parish San Juan de Pastocalle same that had an objective the evaluation of the damage index of pests and diseases in the cultivation of chocho (Lupinus mutabilis) by means of geographic information system programs in order to combat the main problem in agriculture, the effect of the chemical products and pests thus mitigating the environmental problem. In the investigation agriculture 4.0 was used, which complies with the management of technological equipment and software, such as the drone, multispectral cameras, and SIG programs like that the ArcGIS and R for the interpretation. To do this, images of the crop were taken with the help of the drone from different points of view, in order to obtain the NDVI (normalized differential vegetation Index), that trough quantitative values helped us ti differentiate the healthy vegetation from the diseased vegetation, for making a better decision regarding the applications of chemical products, thus eliminat ing some possible physiopathies in lupine cultivation. The results show us that the management of technology in agriculture is efficient, and he can be highlighted in other areas, in addition to the effect of pests, it can be efficient in problem such as water, or possible nutritional deficiencies of crops. The research project has strong impacts on production, social, economic, technological and environmental aspects for the benefit of the producer. It is expected that the results obtained in the research contribute or be a source of incentive to incorporate agricultura 4.0 as a new agricultural model in the region.